Building and monitoring an event-driven microservices ecosystem - Santos, Pedro Aguiar Sousa Moreira dos (2021)
Throughout the years, software architectures have evolved deeply to attempt to address the main issues that have been emerging, mainly due to the ever-changing market needs. The need to provide a way for organizations and teams to build applications independently and with greater agility and speed led to the adoption of microservices, particularly endorsing an asynchronous methodology of communication between them via events. Moreover, the evergrowing demands for high-quality resilient and highly available systems helped pave the path towards a greater focus on strict quality measures, particularly monitoring and other means of assuring the well-functioning of components in production in real-time. Although techniques like logging, monitoring, and alerting are essential to be employed for each microservice, it may not be enough considering an event-driven architecture. Studies have shown that although organizations have been adopting this type of software architecture, they still struggle with the lack of visibility into end-to-end business processes that span multiple microservices. This thesis explores how to guarantee observability over such architecture, thus keeping track of the business processes. It shall do so by providing a tool that facilitates the analysis of the current situation of the ecosystem, as well as allow to view and possibly act upon the data. Two solutions have been explored and are therefore presented thoroughly, alongside a detailed comparison with the purpose of drawing conclusions and providing some guidance to the readers. These outcomes that were produced by the thesis resulted in a paper published and registered to be presented at this year’s edition of the SEI hosted at ISEP.